IDENTIFICATION OF SUBSURFACE LAYERS BY GEOELECTRIC METHOD FOR SLOPE STABILITY ANALYSIS IN LABUAN BULAN HILL, SALEM DISTRICT, REGENCY BREBES, CENTRAL JAVA - Khalifah Buwana Y P, Muhammad
Labuan Hill has a high level of susceptibility to landslide. This is also proven by the presence of cracks that appear. In this study, the identification of the subsurface layer was carried out using the Wenner configuration geoelectric survey method. Geoelectric surveys were carried out on two passes with a track length of 240 m each with an electrode spacing of 5 m. The measurement results identified that the upper layer consists of completely weathered volcanic breccia - residual soil (silty sand) with a resistivity of 285 - 1700 ?m, the second layer is a medium weathered volcanic breccia - strong with a resistivity of 129 - 285 ?m, and the third layer is a fresh volcanic breccia - lightly weathered with a resistivity of 285 - 1388 ?m. Slope stability analysis is carried out using the limit equilibrium method by considering the equilibrium of moments and forces. The analysis was carried out by considering static and dynamic conditions and considering the depth of the groundwater level of natural conditions and conditions with slopes reaching fully saturated conditions. The safety factors obtained on static condition slopes with natural groundwater levels and fully saturated slope conditions, are 1,425 and 1,111. The safety factors obtained on dynamic slope conditions with natural groundwater levels and water-saturated slope conditions, are 1,292 and 1,005. Based on this analysis, the slope is declared safe in static and dynamic conditions at the natural groundwater level and the slope is declared critical in static and dynamic conditions with fully saturated conditions.